Effect of dietary β-1,3-glucan supplementation and heat stress on growth performance, nutrient digestibility, meat quality, organ weight, ileum microbiota, and immunity in broilers - Song Zhang; Jiwen Ou; Zheng Luo; In Ho Kim (Poultry Science, 2020)
The objective of this study was to determine the effect of dietary β-1,3-glucan supplementation and heat stress (HS) on growth performance, nutrient digestibility, meat quality, organ weight, ileum microbiota, and immunity in broiler. A total of 1,440 1-day-old Ross 308 male chicks with an average initial BW of 43.06 ± 1.94 g were sorted into 6 (2 × 3) treatments, 14 replications per treatment. This trail included 2 factors: the dosage of β-1,3-glucan (0, 100 g/T, and 200 g/T) and feeding condition (HS and normal). During the whole trial, significant impacts were observed in BW gain, feed intake，feed conversion rate, and the digestibility of DM and energy between normal treatments and HS treatments (P < 0.05). From day 21 to 35, HS-challenged birds fed the diet with 200 g/T β-1,3-glucan had a lower feed conversion rate than those fed the diet with 0 or 100 g/T β-1,3-glucan (P < 0.05). Moreover, the HS-exposed birds that fed the diet with β-1,3-glucan indicated a greater energy digestibility than those fed the nontreatment diet (P < 0.05). Besides, β-1,3-glucan supplementation could elevate meat pH of all birds and decrease cooking loss significantly of HS-exposed birds (P < 0.05). The HS birds fed the β-1,3-glucan diet obtained a reduced amount of Escherichia coli in the ileum than those fed the nontreatment diet (P < 0.05). Besides, β-1,3-glucan supplementation lowered the level of tumor necrosis factor-α in HS-exposed birds significantly (P < 0.05). These results indicated 100 and 200 g/T β-1,3-glucan supplementation, under HS condition or not, can increase growth performance without a negative response on immunity. Under HS condition, the addition of β-1,3-glucan at dosage from 100 to 200 g/T in the diet can increase energy digestibility, decrease cooking loss, reduce E. coli mount in the ileum, and the tumor necrosis factor-α concentration.